Enterprise Business Architecture: The Formal Link between Strategy and Results - Whittle, Ralph (CRC Press, 2009)
A critical part of any company's successful strategic planning is the creation of an Enterprise Business Architecture (EBA) with its formal linkages. Strategic research and analysis firms have recognized the importance of an integrated enterprise architecture and they have frequently reported on its increasing value to successful companies. Enterprise Business Architecture: The Formal Link between Strategy and Results explains the approach needed for the development of a formal but pragmatic EBA.